Stochastic job stream scheduling method for cipher chip with multi-cryptography - Li LI; Guo-zhen SHI; Kui GENG; Xiu-ze DONG; Xuan WANG; Feng-hua LI (Tongxin xuebao)
Aiming at the rich of safety requirements of tasks which resulting in random cross access to multi cipher algorithms, a hierarchical hardware scheduling method was presented with associated control based on data identifica-tion. The first level was responsible for distributing tasks to different cipher clusters, and by optimizing the search logic to achieve rapid distribution of data. The second level was responsible for completing the context-related tasks in scheduling order by adding an association control module and association queues. Intermediate state storage module realized the saving of the intermediate state in serial cipher algorithm modes, which was indexed by task ID. Pre-processing module process data inputted by the succeeding tasks. It is proved that the proposed scheduling algo-rithm solves the problem of random cross encryption and decryption in many-to-many communication model of high-speed data stream.